Integrating the graduation approach into a sustainable livelihood program - Ito, Yukiko; Shrestha, Dristy; Valenzuela, Jr., Joven (Mandaluyong City, Metro Manila Asian Development Bank, 2023)
This brief shows how the graduation approach can be successfully integrated into sustainable livelihood programs to bolster the incomes and resilience of vulnerable households.
Keywords: Poverty -- Philippines; Social development and protection -- Philippines; Social protection -- Philippines